About the French primary school teacher’s history: “universitarization”, professionalization and relative deprofessionalization (end of XIXth – beginning of XXIth century) (Revista Lusófona de Educação, 2018)
In the last quarter of the twentieth century, the “universitarization” of the French primary teachers (“instituteurs”) training triggered a profound change in their professional identity, which has been widely described and analysed by the literature. Insofar as, from a sociological point of view, the notion of professionalization process calls for comparisons between an earlier state and a present state of a profession in terms of actual status and symbolic recognition between the profession itself and the neighbour and / or rival professions, one can first emphasize the gains of professionalization obtained in a few decades by the “instituteurs”. However, each process positively evaluated resulting in more or less favourable results, it is possible to identify elements in the direction of a certain deprofessionalization understood from the same sociological perspective. Indeed, during the last two decades, the managerial turn and the rise of accountability have strongly affected the professional autonomy of teachers. Some interviews we have driven show this tendency to a form of deprofessionalization.Keywords: french primary teachers; deprofessionalization; professionalization; professional project.